2022
DOI: 10.1155/2022/9885540
|View full text |Cite|
|
Sign up to set email alerts
|

A Study on the Impact of Perioperative Pain Care Management on Pain, Comfort, and Defecation of Patients in Anorectal Surgery

Abstract: Purpose. The aim of the study is to explore the impact of perioperative pain care management on patients’ pain, comfort, and defecation in anorectal surgery. Methods. From January to December 2021, 126 patients who underwent anorectal surgery in our department were selected for the study and were randomly divided into a study group and a control group of 63 patients each after consent was obtained from the patients. The control group was given the usual care protocol and the study group was given the periopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…Bahkan menurut Liao et al (2022) hal tersebut dapat mempengaruhi fisik dan menyebabkan kelainan mental yang dapat mempengaruhi prognosis penyakit dan kualitas hidup pasien. Selain itu, kulit dan area perianal yang banyak terdapat saraf dan pembuluh darah membuat area tersebut menjadi lebih sensitif terhadap rasa sakit (Liao et al, 2022).…”
unclassified